Failures observed in the care of non-effective donors and the psychosocial needs pointed out by their family members: Why did they not donate? - Rodrigues, Simey de Lima Lopes; Boin, Ilka de Fatima Santana Ferreira; Zambelli, Helder Jose Lessa; Sardinha, Luiz Antônio da Costa; Fernandes, Marli Elisa Nascimento (Brazilian Journal of Transplantation, 2020)
Purpose: To verify the perception of non-donor families regarding the care received during the hospitalization of their loved one, the non-effective donor, as well as to know the need for care demanded by family members who experienced such process. Method: Exploratory study with a qualitative approach with ten family members who refused to donate organs and tissues interviewed in 2015. Through semi-structured interviews, sociodemographic data were collected from family members, related to the family experience of the hospitalization. The speech material was transcribed and submitted to an analysis of the thematic content. Results: The following categories were found: family dissatisfaction with the services provided in the emergency units, perception of the need for psychological and social support manifested by the non-donor family, the need to humanize the donation process and suggestions made by family members to improve the process of donation. Conclusions: Participants pointed out failures in the care of the potential donor, from the first care provided in the emergency units in relation to the technical and humanistic ability; there was a major need to humanize the relationships between health professionals and family members in intensive care environments that kept the time and number of visits constraints, and in clarifying information to family members; those families became ill and there was no socio-emotional support after experiencing this process. In addition, we believe that health care practices can be discussed to increase social awareness on this topic and to ensure the care for those families, and this can contribute to the improvement of the donation rates in Brazil.